Phosphorylcholine-conjugated gold-molecular clusters improve signal for Lymph Node NIR-II fluorescence imaging in preclinical cancer models - Baghdasaryan, Ani; Wang, Feifei; Ren, Fuqiang; Ma, Zhuoran; Li, Jiachen; Zhou, Xueting; Grigoryan, Lilit; Xu, Chun; Dai, Hongjie (Nature communications, 2022)
Sentinel lymph node imaging and biopsy is important to clinical assessment of cancer metastasis, and novel non-radioactive lymphographic tracers have been actively pursued over the years. Here, we develop gold molecular clusters (Au 25 ) functionalized by phosphorylcholine (PC) ligands for NIR-II (1000–3000 nm) fluorescence imaging of draining lymph nodes in 4T1 murine breast cancer and CT26 colon cancer tumor mouse models. The Au-phosphorylcholine (Au-PC) probes exhibit ‘super-stealth’ behavior with little interactions with serum proteins, cells and tissues in vivo, which differs from the indocyanine green (ICG) dye. Subcutaneous injection of Au-PC allows lymph node mapping by NIR-II fluorescence imaging at an optimal time of ~ 0.5 − 1 hour postinjection followed by rapid renal clearance. Preclinical NIR-II fluorescence LN imaging with Au-PC affords high signal to background ratios and high safety and biocompatibility, promising for future clinical translation. Fluorescent tracers facilitate the identification and subsequent collection of tumour draining lymph node biopsies, enabling important clinical assessment. Here, the authors present a molecular gold nanocluster NIR-II fluorescent imaging probe and demonstrate its utility to visualise draining lymph nodes in breast and colon cancer mouse models.